Martin Bucer’s Doctrine of Justification: Reformation Theology and Early Modern Irenicism. By Brian Lugioyo - Graybill, Gregory (The journal of theological studies, 2011)
‘Bucer, the rascal, has absolutely lost all my confidence. I shall never trust him. He has betrayed me too often.’ Luther’s words have shaped much scholarly opinion for centuries, and although Brian Lugioyo quotes them (p. 204), he spends the rest of the book seeking to refute them. Was Martin Bucer ‘a theological lightweight, a Vermittlungstheologe, rightly placed in the shadow of Luther and Calvin’ (p.